Metrology Needs for Predicting Concrete Pumpability - Myoungsung Choi; Chiara F. Ferraris; Nicos S. Martys; Didier Lootens; Van K. Bui; H. R. Trey Hamilton (Advances in Materials Science and Engineering)
With the increasing use of pumping to place concrete, the development and refinement of the industry practice to ensure successful concrete pumping are becoming important needs for the concrete construction industry. To date, research on concrete pumping has been largely limited to a few theses and research papers. The major obstacle to conduct research on concrete pumping is that it requires heavy equipment and large amounts of materials. Thus, developing realistic and simple measurement techniques and prediction tools is a financial and logistical challenge that is out of reach for small research labs and many private companies in the concrete construction industry. Moreover, because concrete pumping involves the flow of a complex fluid under pressure in a pipe, predicting its flow necessitates detailed knowledge of the rheological properties of concrete, which requires new measurement science. This paper summarizes the technical challenges associated with concrete pumping and the development in concrete pumping that have been published in the technical literature and identifies future research needed for the industry to develop best practices for ensuring successful concrete pumping in the field.